2006
DOI: 10.1002/zaac.200500471
|View full text |Cite|
|
Sign up to set email alerts
|

New Saccharinato/Ammonia Complexes of Nickel(II) and Zinc(II). A Structural and Spectroscopic Study

Abstract: Two new saccharinate/NH 3 complexes of composition [Ni(sac) 2 (NH 3 ) 4 ] and [Zn(sac) 2 (NH 3 ) 2 ] were obtained and their crystal structures determined by single crystal X-ray diffractometry. The elongated octahedral Ni II complex crystallizes in the monoclinic P2 1 /c space group with Z ϭ 2 whereas the tetrahedral Zn II complex is triclinic (space group P1 and Z ϭ 2). For [Ni(sac) 2 -619 (NH 3 ) 4 ] the magnetic moment and electron absorption spectrum were obtained and discussed. The infrared spectra of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Sodium saccharin affects the ion deposition process by forming ion complexes, ion-pairing, and interacting with the substrate to block particular surface sites. 32 Thus, the addition of saccharin in the electrodeposition process of the metals Zn and Ni can guide a uniform deposition of metal ions, which reduces the stress of the coating, produces deposition products with smooth, fine grains and compact morphology, and finally greatly improves the corrosion resistance. 33 Lokhande et al and Singh et al reported that saccharin molecules would have characteristic adsorption on the electrode, with which the electrochemical activity was improved and corrosion was reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium saccharin affects the ion deposition process by forming ion complexes, ion-pairing, and interacting with the substrate to block particular surface sites. 32 Thus, the addition of saccharin in the electrodeposition process of the metals Zn and Ni can guide a uniform deposition of metal ions, which reduces the stress of the coating, produces deposition products with smooth, fine grains and compact morphology, and finally greatly improves the corrosion resistance. 33 Lokhande et al and Singh et al reported that saccharin molecules would have characteristic adsorption on the electrode, with which the electrochemical activity was improved and corrosion was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination chemistry of this sodium saccharin-dissociated anion is very interesting and versatile, considering that it has different coordination positions in the metal center. Sodium saccharin affects the ion deposition process by forming ion complexes, ion-pairing, and interacting with the substrate to block particular surface sites . Thus, the addition of saccharin in the electrodeposition process of the metals Zn and Ni can guide a uniform deposition of metal ions, which reduces the stress of the coating, produces deposition products with smooth, fine grains and compact morphology, and finally greatly improves the corrosion resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, saccharinate is coordinated by either N-monodentate or O-monodentate with nickel. [19][20][21] Of these, the N-bound form is more common; the O-bound complex through the carbonyl oxygen is unusual and is found when branched or bulky coligands are present. 16 The structures adopted by saccharin on metal electrode surfaces have been examined using scanning tunnel microscopy ͑STM͒.…”
mentioning
confidence: 99%